The Metastatic Cascade as the Basis for Liquid Biopsy Development - Eslami-S, Zahra; Cortés-Hernández, Luis Enrique; Alix-Panabières, Catherine (Frontiers in Oncology, 2020)
The metastatic cascade describes the process whereby aggressive cancer cells leave the primary tumor, travel through the bloodstream, and eventually reach distant organs to develop one or several metastases. During the last decade, innovative technologies have exploited the recent biological knowledge to identify new circulating biomarkers for the screening and early detection of cancer, real-time monitoring of treatment response, assessment of tumor relapse risk (prognosis), identification of new therapeutic targets and resistance mechanisms, patient stratification and therapeutic decision-making. These techniques are broadly described using the term of Liquid Biopsy. This field is in constant progression and is based on the detection of circulating tumor cells, circulating free nucleic acids (e.g. circulating tumor DNA), circulating tumor-derived extracellular vesicles, and tumor-educated platelets. The aim of this review is to describe the biological principles underlying the liquid biopsy concept, and to discuss how functional studies can expand the clinical applications of these circulating biomarkers.